Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445088
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Expertise and Roles: A Framework to Characterize the Stakeholders of Interpretable Machine Learning and their Needs

Abstract: To ensure accountability and mitigate harm, it is critical that diverse stakeholders can interrogate black-box automated systems and find information that is understandable, relevant, and useful to them. In this paper, we eschew prior expertise-and role-based categorizations of interpretability stakeholders in favor of a more granular framework that decouples stakeholders' knowledge from their interpretability needs. We characterize stakeholders by their formal, instrumental, and personal knowledge and how it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 121 publications
(267 reference statements)
0
51
0
Order By: Relevance
“…Nevertheless, given the potentially severe consequences of an incorrect prediction, we consider it essential to present additional context for predictions from all AA methods. While the exact context needs to be tailored to the intended application and user (Suresh et al, 2021), authors should include calculated metrics or predictors and any easily obtained fixed or learned thresholds.…”
Section: Which Sample Of Assessments Is Most Effective For Training and Evaluating Aa Methods?mentioning
confidence: 99%
“…Nevertheless, given the potentially severe consequences of an incorrect prediction, we consider it essential to present additional context for predictions from all AA methods. While the exact context needs to be tailored to the intended application and user (Suresh et al, 2021), authors should include calculated metrics or predictors and any easily obtained fixed or learned thresholds.…”
Section: Which Sample Of Assessments Is Most Effective For Training and Evaluating Aa Methods?mentioning
confidence: 99%
“…The formative study has two parts: we first thoroughly surveyed relevant literature [5,29,31,35,37,38,42,55] and industrial standard documentations [1,2,18,36] to understand how a presentation deck looks like, and what contents are usually included. Based on these insights, we drafted an presentation outline to represent a common presentation structure.…”
Section: Formative Studymentioning
confidence: 99%
“…Some prior works reported that DS workers might spend hours or even days to prepare the presentation slide after they finish their core technical modeling works [38]. The work is tedious and time-consuming due to multiple reasons: a) data scientists have to meticulously locate and distill essential information from the complex, messy, and sometimes fragmented experimental codes [29,39]; b) they need to organize these information to construct a story narrative; and, c) they also need to consider the specific domain context and audience backgrounds, and often add additional information (e.g., visualizations, explanations, and examples) to customize their presentation so that it can better engage the target audience and gain their trust [8,29,42].…”
Section: Introductionmentioning
confidence: 99%
“…It is of particular importance to investigate end user characteristics specifically in the clinical context of the chosen task. This is because, depending on the task, stakeholders have varied interest, prior knowledge, responsibilities, and requirements [92].…”
Section: Intrprt Guidelinementioning
confidence: 99%
“…More specialized guidelines are required for high-risk domains. Similarly, previous attempts to guide the design of effective transparency mechanisms acknowledge that real stakeholders involved should be considered and understood [92,53,101]. Starting from the identification of diverse design goals according to users' needs and their level of expertise on AI technology, and a categorization of evaluation measures for Explainable Artificial Intelligence (XAI) systems, [67] addressed the multidisciplinary efforts needed to build such systems.…”
Section: Increasing Demand For Guidelines To Build ML Systemsmentioning
confidence: 99%